Trace Si-induced interfacial anchoring stabilizes Cu–CeO2 active sites for durable high-temperature reverse water–gas shift reaction - Linyu Zhang; Lulu Zhou; Liang Yuan; Haohao Feng; Jingfeng Han; Yongdong Chen (Chemical Engineering Journal, 2026)

Carbon/nitrogen composite induction of extracellular polymeric substances from Desulfovibrio desulfuricans enables Cu2S quantum dot biosynthesis - Guangwen Zheng; Weifeng Song; Zuoyi Yang; Yantong Gao; Qian Yin; Ziheng Song; Chuanying Tu; Keqin Zhou; Junming Bian; Jingfeng Peng; Xiangdan Zhang; Xiaoyan Bai (Journal of Environmental Chemical Engineering, 2026)

Developmental toxicity assessment of Allura Red AC in SD rats: A focus on skeletal ossification - Penghe Liu; Fang Tan; Jingfeng Sun; Yanwu Wang; Liying Zhou; Danlian Liang; Guangqiu Qin (Reproductive Toxicology, 2026)

Constructing electronic-ionic bicontinuous networks for high-fidelity bioelectrical monitoring with 24-hour stable interfaces - Guangyuan Xu; Chuantian Ren; Weiguang Wang; Yufeng Wu; Yiqian Zhou; Ming Lei; Jingfeng Zhang; Kai Huang; Hui Wu (Chemical Engineering Journal, 2026)

Stock-scale scenario analysis of retrofit impacts on operational energy demand and carbon emissions in hotels across England and Wales - Jingfeng Zhou; Pamela Fennell; Ivan Korolija; Paul Ruyssevelt (Building and Environment, 2026)

Dual regulation of EPS protein structure by C/S composite induction enables controlled biosynthesis of ZnS quantum dots - Chuanying Tu; Zuoyi Yang; Weifeng Song; Guangwen Zheng; Jingfeng Peng; Keqin Zhou; Junming Bian; Yantong Gao; Qian Yin; Xiangdan Zhang; Xiaoyan Bai (Journal of Water Process Engineering, 2026)

Large language model orchestrated workflow integrating retrieval-augmented generation and model context protocol tools for urban-scale simulation-based resilience assessment - Jingfeng Zhou; Jiying Chen; Meng Wang; Baihua Dong; Xiaochi Zhou (Building and Environment, 2026)

Spatiotemporal pattern of wheat harvest duration and its driving factors in the Huang-Huai-Hai plain of China - Renhai Zhong; Cong Chen; Guan Zhou; Xingguo Xiong; Qiyu Tian; Jingfeng Huang; Guangqiao Cao; Tao Lin (Computers and Electronics in Agriculture, 2026)

KLF9 Aggravates Doxorubicin-Induced Cardiotoxicity by Regulating the ROS/p53 Signalling Pathway - Jingfeng Peng; Jianhua Wang; Hui Feng; Bihan Zhou; Haoyu Zhou; Fangfang Li (Cardiovascular Toxicology, 2026)

Multi-satellite derived data reveals spatiotemporal dynamics of carbon-water coupling and its drivers in tropical ecosystems - Xiang Wang; Zheng Fu; Philippe Ciais; Josep Peñuelas; Jingfeng Xiao; Xing Li; Xiangzhong Luo; Chi Chen; Haoyu Xia; Tao Zhou; Paul C. Stoy; Julia K. Green; et al. (Remote Sensing of Environment, 2026)

The dual role of water in CO2 capture by a novel 2-(ethylamino)ethanol-based non-aqueous phase-change absorbent: A net positive effect - Dunqiu Wang; Jingfeng Shen; Dan Wang; Yinming Fan; Shengpeng Mo; Bihong Lv; Yanan Zhang; Yinian Zhu; Zongqiang Zhu; Mi Feng; Xiaobin Zhou; Guohua Jing (Chemical Engineering Journal, 2025)

Pre-occupation strategy towards high initial coulombic efficiency in Mn-based layer cathode for magnesium-based hybrid-ion batteries - Yipeng Liu; Baihua Qu; Junhao Zhang; Hongfei Zheng; Le Tong; Yue Hao; Dong Wang; Guangsheng Huang; Qian Li; Xiaoyuan Zhou; Dong-Liang Peng; Jingfeng Wang (Chemical Engineering Journal, 2025)

Projecting city-scale energy performance under future weather scenarios through urban building energy modelling incorporating cluster archetypes - Jingfeng Zhou; Jiying Chen; Kaixuan Wang; Bingyu Xu; Xuhui Lin; Jiayi Yan; Meng Wang (Sustainable Cities and Society, 2025)

Biases in radiative flux observations due to precipitation across the Arctic forest-tundra ecotone - Taeho Kim; Wenbo Zhou; Vinh Ngoc Tran; Liujing Zhang; Jingfeng Wang; Modi Zhu; Aleksey Y. Sheshukov; Tianqi Zhang; Desheng Liu; Valeriy S. Mazepa; Alexandr A. Sokolov; Victor V. Valdayskikh; et al. (Agricultural and Forest Meteorology, 2025)

C/S composite induction on spatial structure of EPS from Desulfovibrio desulfuricans subsp. and their adsorption performance of Zn(II) - Chuanying Tu; Zuoyi Yang; Weifeng Song; Guangwen Zheng; Jingfeng Peng; Keqin Zhou; Junming Bian; Xiangdan Zhang; Xiaoyan Bai (Journal of Water Process Engineering, 2025)

The Sustained-Release Oxygen Granule Preparation and Its Application in the Transportation of Live Sea Cucumber Apostichopus Japonicus - Yimeng Li; Jinghe Sun; Yan Zhou; Liming Sun; Jingfeng Yang (Journal of Aquatic Food Product Technology, 2025)

Climate change impacts on city-scale building energy performance based on GIS-informed urban building energy modelling - Meng Wang; Jingfeng Zhou; Yujing Liang; Hang Yu; Rui Jing (Sustainable Cities and Society, 2025)

Reduced Erosion Augments Soil Carbon Storage Under Cover Crops - Wenjuan Huang; Lifen Jiang; Jian Zhou; Hyung‐Sub Kim; Jingfeng Xiao; Yiqi Luo (Global Change Biology, 2025)
Cover crops, a promising strategy to increase soil organic carbon (SOC) storage in croplands and mitigate climate change, have typically been shown to benefit soil carbon (C) storage from increased plant C inputs. However, input‐driven C benefits may be augmented by the reduction of C outputs induced by cover crops, a process that has been tested by individual studies but has not yet been synthesized. Here we quantified the impact of cover crops on organic C loss via soil erosion (SOC erosion) and revealed the geographical variability at the global scale. We analyzed the field data from 152 paired control and cover crop treatments from 57 published studies worldwide using meta‐analysis and machine learning. The meta‐analysis results showed that cover crops widely reduced SOC erosion by an average of 68% on an annual basis, while they increased SOC stock by 14% (0–15 cm). The absolute SOC erosion reduction ranged from 0 to 18.0 Mg C −1 ha −1 year −1 and showed no correlation with the SOC stock change that varied from −8.07 to 22.6 Mg C −1 ha −1 year −1 at 0–15 cm depth, indicating the latter more likely related to plant C inputs. The magnitude of SOC erosion reduction was dominantly determined by topographic slope. The global map generated by machine learning showed the relative effectiveness of SOC erosion reduction mainly occurred in temperate regions, including central Europe, central‐east China, and Southern South America. Our results highlight that cover crop‐induced erosion reduction can augment SOC stock to provide additive C benefits, especially in sloping and temperate croplands, for mitigating climate change.

Percentage-based thermal zoning approach for enhanced stock-level building energy performance modelling - Jingfeng Zhou; Pamela Fennell; Ivan Korolija; Paul Ruyssevelt (Energy and Buildings, 2025)

Rising Atmospheric CO 2 Alleviates Drought Impact on Autumn Leaf Senescence Over Northern Mid‐High Latitudes - Peng Li; Mai Sun; Jingfeng Xiao; Yunpeng Luo; Yao Zhang; Xing Li; Xiaolu Zhou; Changhui Peng (Global Ecology and Biogeography, 2025)
Aim Drought reduces plant growth and hastens the process of leaf senescence in autumn. Concurrently, increasing atmospheric CO 2 concentrations likely amplifies photosynthetic activity while increasing plant water‐use efficiency. However, how drought affects the date of leaf senescence (DLS) and whether elevated CO 2 can alleviate this remain unknown. Here, we explore the effect of drought on DLS under recent climate change and explore the underlying mechanisms. Location Northern mid‐high latitudes. Time Period 2000–2019. Major Taxa Studied Plants. Methods We conducted comprehensive analyses based on satellite remote sensing, eddy covariance flux observations, in situ phenology observations and land‐surface models. Linear regression analysis and a ten‐year moving window were adapted to investigate the spatiotemporal patterns in DLS sensitivity to drought ( S dd ). The partial least squares regression method was used to attribute the main factors for the variation in S dd , and land‐surface models in different scenarios were used to verify the robustness of the results. Results Our study presented divergent spatial patterns of S dd , where the highest S dd was concentrated in dry and warm regions. Temporally, multiple datasets consistently illustrate a significant decrease in the S dd during recent decades ( p S dd and aridity gradient, which presented a slightly positive S dd trend in dry regions but a negative trend in wet regions. We found these observed changes were primarily attributed to elevated CO 2 , alleviating the drought stress on DLS in nearly 40% of the study area. Main Conclusions Our findings demonstrate the complex role that atmospheric CO 2 plays in regulating plant leaf senescence during drought stress, highlighting the need to incorporate the effects of elevated CO 2 on vegetation autumn phenology into land‐surface models for projecting vegetation growth and carbon uptake under continued global change.

Examining the impact of common faults on chiller performance through experimental investigation and parameter sensitivity analysis - Zhanwei Wang; Penghua Xia; Sai Zhou; Lin Wang; Jingjing Guo; Xiuzhen Li; Jingfeng Shi; Jianxing Chen (Energy and Buildings, 2024)

Oxygenated storage alleviates autolysis of the sea cucumber Apostichopus japonicus during transport - Yan Zhou; Jie Zheng; Jun Zhao; Shuang Li; Jie Xing; Chunqing Ai; Chenxu Yu; Sheng Yang; Jingfeng Yang (Aquaculture International, 2023)

Large discrepancies among remote sensing indices for characterizing vegetation growth dynamics in Nepal - Decheng Zhou; Liangxia Zhang; Lu Hao; Ge Sun; Jingfeng Xiao; Xing Li (Agricultural and Forest Meteorology, 2023)

Counting piglet suckling events using deep learning-based action density estimation - Haiming Gan; Jingfeng Guo; Kai Liu; Xinru Deng; Hui Zhou; Dehuan Luo; Shiyun Chen; Tomas Norton; Yueju Xue (Computers and Electronics in Agriculture, 2023)

Accident pattern recognition in subway construction for the provision of customized safety measures - Haonan Qi; Zhipeng Zhou; Jingfeng Yuan; Nan Li; Jianliang Zhou (Tunnelling and Underground Space Technology, 2023)

Pheromone effect of estradiol regulates the conjugative transfer of pCF10 carrying antibiotic resistance genes - Xiaobo Yang; Yuanyuan Niu; Yutong Yang; Hongrui Zhou; Jing Li; Xinyue Fu; Zhiqiang Shen; Jingfeng Wang; Zhigang Qiu (Journal of Hazardous Materials, 2023)

Docosahexaenoic acid inhibits pheromone-responsive-plasmid-mediated conjugative transfer of antibiotic resistance genes in Enterococcus faecalis - Hongrui Zhou; Xiaobo Yang; Yutong Yang; Yuanyuan Niu; Jing Li; Xinyue Fu; Shang Wang; Bin Xue; Chenyu Li; Chen Zhao; Xi Zhang; Zhiqiang Shen; et al. (Journal of Hazardous Materials, 2023)

Accumulated soil moisture deficit better indicates the effect of soil water stress on light use efficiency of grasslands during drought years - Zhenyu Zhang; Yanlian Zhou; Weimin Ju; Jingming Chen; Jingfeng Xiao (Agricultural and Forest Meteorology, 2023)

Experimental research on the performance and parameters sensitivity analysis of variable refrigerant flow system with common faults imposed in heating mode - Wei Gou; Zhaoting Ren; Huanxin Chen; Lu Xing; Zhenxin Zhou; Xingxiang Xia; Jingfeng Shi (Energy and Buildings, 2023)

Divergent responses of autumn vegetation phenology to climate extremes over northern middle and high latitudes - Mei Wang; Peng Li; Changhui Peng; Jingfeng Xiao; Xiaolu Zhou; Yunpeng Luo; Cicheng Zhang (Global Ecology and Biogeography, 2022)
Aim Compared with gradual climate change, extreme climatic events have more direct and dramatic impacts on vegetation growth. However, the influence of climate extremes on important phenological periods, such as the end of the growing season (EOS), remains unclear. Here, we investigate the temporal trends of EOS across different biomes and quantify the response of EOS to multiple climate extreme indices (CEIs). Location Northern middle and high latitudes. Time period 2000–2020. Major taxa studied Plants. Methods Three phenology extraction methods were used to compute EOS from satellite, FLUXNET and Pan European Phenology Project PEP725 phenological datasets. Different stress states of cold, hot, dry and wet extremes were represented by 12 CEIs. Partial correlation and ridge regression analysis were used to quantify the response of EOS to climate extremes across latitudinal and biome scales. Results Our study showed a delayed EOS in boreal biomes, but a significantly advanced EOS in temperate biomes. The advanced EOS induced by cold stress was observed for c . 80% of the vegetated pixels. The warm‐related CEIs delayed the EOS in high latitudes, and the delayed effect weakened or even reversed with decreasing latitude. In contrast, EOS exhibited opposite response patterns to dry days and wet‐related CEIs. Overall, EOS exhibited higher sensitivity to extreme temperature in boreal biomes than in temperate biomes. Specifically, continuous drought and high heat stress induced an earlier EOS in some temperate forest biomes, whereas moderate heat stress delayed the EOS in most study biomes. In contrast, EOS was not sensitive to extreme drought in water‐restricted biomes. Main conclusions EOS exhibited divergent responses to various climate extremes with different intensities and frequencies. Moreover, the response of EOS to extreme climate stress was dependent on the biome and latitude. These findings emphasize the importance of incorporating the divergent extreme climate effects into vegetation phenological models and Earth system models.

Pseudoephedrine hydrochloride causes hyperactivity in zebrafish via modulation of the serotonin pathway - Yini Zhou; Tonglaga Li; Shangzi Zhou; Han Xu; Xiaoyu Yin; Hao Chen; Xuan Ni; Meirong Bai; Wuliji Ao; Jingfeng Yang; R. G. Ahmed; Xuefu Zhang; et al. (Metabolic Brain Disease, 2022)

Rapid detection method of Skeletonema pseudocostatum and preparation of test strip - Haoran Li; Kun Meng; Qiaojie Yu; Changping Chen; Jingfeng Chen; Jingli Li; Xinyi Wang; Yingzi Wang; Mingyang Li; Chuang Chen; Kefu Zhou (Environmental Science and Pollution Research, 2022)

Potato (Solanum tuberosum L.) non-specific lipid transfer protein StLTP6 promotes viral infection by inhibiting virus-induced RNA silencing - Kaijie Shang; Yang Xu; Weilin Cao; Xiaoying Xie; Yanru Zhang; Jingfeng Zhang; Hongmei Liu; Shumei Zhou; Xiaoping Zhu; Changxiang Zhu (Planta, 2022)

Aberrant DNA methylation in t(8;21) acute myeloid leukemia - Shujiao He; Jingfeng Zhou; Li Yu (Genome Instability & Disease, 2022)
Aberrant DNA methylation is a hallmark of acute myeloid leukemia (AML). Various studies showed that t(8;21) AML presented a distinct DNA methylation profile and could be categorized into a separate cluster according to DNA methylation sequencing. Yet, there is still a lack of understanding regarding the causes and mechanisms of this phenomenon. Knowing how the DNA methylation is regulated in t(8;21) AML would enhance our understanding of leukemogenesis and may assist clinical decision-making regarding DNA methylation-targeted therapy. Herein, we summarized our current knowledge concerning DNA methylation regulation in t(8;21) AML and discussed their potential clinical significance in this article.

Expert consensus on organizing the multidisciplinary team (MDT) diagnosis and treatment of hepato-pancreato-biliary diseases in China - Binhao Zhang; Jian Zhou; Weifen Xie; Kaishan Tao; Shichun Lu; Xianglin Yuan; Lianxin Liu; Weilin Wang; Yilei Mao; Ping Bie; Jingfeng Liu; Xinyu Bi; et al. (Science China Life Sciences, 2022)

Characterization of a novel Vibrio parahaemolyticus host-phage pair and antibacterial effect against the host - Chao Gao; Xiaobo Yang; Chen Zhao; Chenyu Li; Shang Wang; Xi Zhang; Bin Xue; Zhuosong Cao; Hongrui Zhou; Yutong Yang; Zhiqiang Shen; Pingfeng Yu; et al. (Archives of Virology, 2022)

Comprehensive evaluation and analysis of the salinity stress response mechanisms based on transcriptome and metabolome of Staphylococcus aureus - Ying Feng; Dizhou Gu; Ziyan Wang; Chenyang Lu; Jingfeng Fan; Jun Zhou; Rixin Wang; Xiurong Su (Archives of Microbiology, 2022)

Isolation and characterization of PoWRKY, an abiotic stress-related WRKY transcription factor from Polygonatum odoratum - Zhongping Wei; Jingfeng Ye; Zhiquan Zhou; Gang Chen; Fanjin Meng; Yifei Liu (Physiology and Molecular Biology of Plants, 2021)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Aberrant interhemispheric functional connectivity in first-episode, drug-naïve major depressive disorder - Hong Yang; Chengwei Wang; Gongjun Ji; Zhan Feng; Jingfeng Duan; Feng Chen; Xiaohong Joe Zhou; Yushu Shi; Haiyan Xie (Brain Imaging and Behavior, 2019)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Impacts of land use and socioeconomic patterns on urban heat Island - Junmei Tang; Liping Di; Jingfeng Xiao; Dengsheng Lu; Yuyu Zhou (International Journal of Remote Sensing, 2017)

Enrichment, Distribution of Vanadium-Containing Protein in Vanadium-Enriched Sea Cucumber Apostichopus japonicus and the Ameliorative Effect on Insulin Resistance - Yanjun Liu; Qingxin Zhou; Yanlei Zhao; Yiming Wang; Yuming Wang; Jingfeng Wang; Jie Xu; Changhu Xue (Biological Trace Element Research, 2016)

Assessment of total and organic vanadium levels and their bioaccumulation in edible sea cucumbers: tissues distribution, inter-species-specific, locational differences and seasonal variations - Yanjun Liu; Qingxin Zhou; Jie Xu; Yong Xue; Xiaofang Liu; Jingfeng Wang; Changhu Xue (Environmental Geochemistry and Health, 2016)

Survival and development of Liaodong oak stump sprouts in the Huanglong Mountains of China six years after three partial harvests - Li Rong; Zhang Wenhui; He Jingfeng; Zhou Jianyun (New Forests, 2013)

Development and evaluation of a new detection tool—visual DNA microarray for simultaneous and specific detection of human immunodeficiency virus type-1 and hepatitis C virus - Jingfeng Tang; Li Zhou; Lian Lian Duan; Yang Feng; Xuan Cao; Yefu Wang (Molecular Biology Reports, 2011)

Forms and balance of nitrogen and phosphorus in cage culture waters in Guangdong Province, China - Yanmao Wen; Xiange Wei; Tingfei Shu; Jingfeng Zhou; Guanghui Yu; Feng Li; Yanyun Huang (Chinese Geographical Science, 2007)